Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1093/nar/gks1289
|View full text |Cite
|
Sign up to set email alerts
|

The high kinetic stability of a G-quadruplex limits hnRNP F qRRM3 binding to G-tract RNA

Abstract: The RNA binding protein heterogeneous nuclear ribonucleoprotein (hnRNP) F is involved in telomeres maintenance and pre-mRNA processing, such as alternative splicing and polyadenylation. It specifically recognizes RNA containing three consecutive guanines (G-tracts) that have the potential to assemble into G-quadruplexes. We have proposed recently that hnRNP F could regulate alternative splicing by remodeling RNA structures, such as G-quadruplexes. However, the exact mechanism of hnRNP F binding to such RNA seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 50 publications
5
41
1
Order By: Relevance
“…An extensive search of the literature did not reveal any evidence about direct protein-protein interactions between FMRP and any of the splicing factors identified by the SFmap software (Supplemental Table 1), suggesting that FMRP might function to control the accessibility of the splicing factors to their RNA binding sites. Supporting this hypothesis are the findings that the binding of hnRNP F to its G-rich RNA binding site is limited by the stability of a G-quadruplex structure adopted by this sequence (Samatanga et al 2012). Specifically, it has been shown that hnRNP F does not bind to the G-quadruplex structure formed by its G-rich binding site, and there is a competition between the formation of the G-quadruplex structure and of the hnRNP F protein-RNA complex.…”
Section: Fbssh Rna Interactions With Different Fmrp Isoformsmentioning
confidence: 99%
“…An extensive search of the literature did not reveal any evidence about direct protein-protein interactions between FMRP and any of the splicing factors identified by the SFmap software (Supplemental Table 1), suggesting that FMRP might function to control the accessibility of the splicing factors to their RNA binding sites. Supporting this hypothesis are the findings that the binding of hnRNP F to its G-rich RNA binding site is limited by the stability of a G-quadruplex structure adopted by this sequence (Samatanga et al 2012). Specifically, it has been shown that hnRNP F does not bind to the G-quadruplex structure formed by its G-rich binding site, and there is a competition between the formation of the G-quadruplex structure and of the hnRNP F protein-RNA complex.…”
Section: Fbssh Rna Interactions With Different Fmrp Isoformsmentioning
confidence: 99%
“…In addition, two mutants with an intact G-tract but predicted to disrupt TCEI stem base pairing, TCE UAC and TCE GAC , retained both higher and lower affinity binding components (Figure S1C, D), indicating that the G-tract sequence is responsible for the higher affinity binding. These data also indicate that Glo can interact with the G-tract regardless of whether it is base-paired and suggest that, like hnRNP F (Dominguez et al 2010; Samatanga et al, 2013), Glo binding may promote a single-stranded configuration of G-tracts.…”
Section: Resultsmentioning
confidence: 69%
“…Recognition of the G-tract is instead mediated by residues located in three loops (Dominguez and Allain, 2006; Dominguez et al, 2010; Honore et al, 1995). The loop residues encage the G-tract, sequestering it in a single-stranded conformation (Dominguez et al, 2010; Samatanga et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In mitochondria, the G-quadruplex structure in RNA facilitates the termination of DNA transcription (42). The RNA G-quadruplex affects alternative splicing, ribosomal frameshifts, and stop codon readthrough (43)(44)(45)(46). In the 3= UTR of mRNAs, the G-quadruplex structure drives subcellular relocalization and increases the efficiency of alternative polyadenylation and therefore the expression of shortened transcripts (47,48).…”
Section: Discussionmentioning
confidence: 99%